2021
DOI: 10.14710/jnc.v10i4.31651
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH JUS KULIT BUAH SEMANGKA (Citrullus lanatus) TERHADAP STATUS HIDRASI ATLET DI UKM SEPAK BOLA

Abstract: Background: Football as a high-intensity sport that causes fluid loss in the body often makes athletes dehydrated which results in decreased athlete performance. Provision of adequate and appropriate drinks can prevent dehydration. Watermelon rind contains high potassium which can restore lost body fluids.Objectives: Conducted a study to determine the correlation of giving watermelon rind juice to the hydration status of athletes in the Student Football Activity Unit.Methods: The study was conducted with a qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Factor analysis of the subject's food intake showed that there was no significant effect between energy, protein, fat and carbohydrate intake with VO 2 max capacity of subjects with p-values of energy 0.356, protein 0.132, fat 0.942 and carbohydrates 0.597 (p>0.05). This result is in line with research Safitri & Dieny (2015); Setiawan (2016); Amin et al (2017) which showed that the intake of energy, protein, fat and carbohydrates did not have a significant effect on the VO 2 max capacity of football athletes. In addition to energy and nutrients such as protein, fat and carbohydrates, the intake of minerals such as magnesium, calcium, sodium and potassium is also a confounding variable in this study.…”
Section: Resultssupporting
confidence: 90%
“…Factor analysis of the subject's food intake showed that there was no significant effect between energy, protein, fat and carbohydrate intake with VO 2 max capacity of subjects with p-values of energy 0.356, protein 0.132, fat 0.942 and carbohydrates 0.597 (p>0.05). This result is in line with research Safitri & Dieny (2015); Setiawan (2016); Amin et al (2017) which showed that the intake of energy, protein, fat and carbohydrates did not have a significant effect on the VO 2 max capacity of football athletes. In addition to energy and nutrients such as protein, fat and carbohydrates, the intake of minerals such as magnesium, calcium, sodium and potassium is also a confounding variable in this study.…”
Section: Resultssupporting
confidence: 90%
“…Antioxidant such as beta-carotene and vitamin C are also found in watermelon albedo, as well as phenols that help maintain healthy somatic cells (Putri et al, 2020). According to Patil (2020), the watermelon skin (albedo) and the fruit flesh are having a non-essential citrulline substance (Setiawan and Widyastuti, 2016). Citrulline in the albedo is approximately 60% higher than in flesh, which is beneficial for heart and immunity (Mawaddah, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Potassium is one of the components of isotonic drinks that binds sodium, chloride, and glucose. Potassium maintains fluid and electrolyte balance and acid-base in the body (Fadlilah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The study from Lutvida (2018), which examined the effect of giving watermelon juice and isotonic drinks on hydration status in 10 male futsal athletes with an average age of 20.5years old in Cimahi City, showed results that giving watermelon juice and isotonic drinks can maintain hydration status and prevent dehydration in futsal athletes. Another study examined the pre-posttest design without control group design on the effect of watermelon peel juice (Citrullus lanatus) on hydration status in 18 student soccer athletes at Universitas Ahmad Dahlan football UKM, showing the results that there was a decrease in the average specific gravity of urine after being given watermelon peel juice (Fadlilah et al, 2021). Based on the background above, there is a need for further testing on the Effect of Isotonic Drink and Yellow Watermelon Juice on the Hydration Status of Semarang Java Futsal and T-Rex Football Players.…”
Section: Introductionmentioning
confidence: 99%